Review of the II International Congress on the History of Turkic Statehood “The statehood of the Turkic peoples in the Chingisid era” - Umbetov N.A. (Золотоордынское обозрение)
From October 4 to 6, 2024, the II International Congress on the History of Turkic Statehood was held in Almaty, Kazakhstan, with the theme “The statehood of the Turkic peoples in the Chingisid era ”, dedicated to the 800th anniversary of the Ulus of Jochi. The Congress was organized by the Turkic Academy in collaboration with the Turkish Historical Society under the Atatürk Supreme Council for Culture, Language, and History and the Research Institute for Jochi Ulus studies, under the Ministry of Science and Higher Education of Kazakhstan. The international event brought together leading scholars, representatives of academic and diplomatic circles from Turkic countries, as well as guests from Mongolia, Korea, Russia, the USA, Austria, Ukraine, France, and Bulgaria, creating a platform for multilateral exchange of opinions and scientific discoveries. The congress presented reports covering a wide range of topics – from analyzing the chronology of key events to examining the political, economic, and cultural processes related to the history of Turkic peoples during the Chingisid era. Special attention was given to key issues concerning the history of the Ulus of Jochi, its role in the formation of Turkic states, as well as the processes of Islamization and Turkification. The congress not only facilitated the exchange of knowledge and scientific discoveries but also laid a strong foundation for future research. An important result was the strengthening of academic ties and international cooperation, opening up prospects for new joint projects and research endeavors aimed at studying the history of Turkic states and their role in world history.